2016
DOI: 10.1002/jor.23170
|View full text |Cite
|
Sign up to set email alerts
|

Radiostereometric analysis using clinical radiographic views: Validation measuring total hip replacement wear

Abstract: Radiostereometric analysis (RSA) is a stereo X-ray technique used in clinical research studies to evaluate micro-motion and wear of orthopaedic implants within bone. While highly accurate and precise, its adoption has been limited due to technical requirements such as the need for implanted marker beads and radiograph view angles determined by a calibration cage. We propose a new technique that separates the calibration procedure from the patient examination, enabling clinical radiograph views to be used for R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The model-based RSA software had higher errors in the anterior axis and resultant 3D measurements. 22 Previously, the accuracy of the RSA method was improved when more markers were used to represent the acetabular component 30,36 but this was not the case in our study. Only one study has compared the accuracy of different acetabular reference segments with and without ellipse algorithms 27 and our study confirmed that there was no significant difference in the accuracy using different representations of the acetabular component (Table 4).…”
Section: Discussionmentioning
confidence: 62%
“…The model-based RSA software had higher errors in the anterior axis and resultant 3D measurements. 22 Previously, the accuracy of the RSA method was improved when more markers were used to represent the acetabular component 30,36 but this was not the case in our study. Only one study has compared the accuracy of different acetabular reference segments with and without ellipse algorithms 27 and our study confirmed that there was no significant difference in the accuracy using different representations of the acetabular component (Table 4).…”
Section: Discussionmentioning
confidence: 62%
“…In our previous study under a CR environment, a numerical registration approach was presented. 17 It first measured the calibration radiographs and phantom images individually, then registered both measurements together numerically. It should be emphasized that these different approaches provide equivalent outcomes in RSA.…”
Section: Discussionmentioning
confidence: 99%
“…It not only reduces the cost for RSA studies but also provides the opportunity to apply a novel RSA method with clinical radiographic views. 12 Furthermore, it makes RSA more accessible to clinics. This novel RSA method separates the calibration radiographic procedure from the patient radiographic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…11 The usage of CR in RSA largely reduces the measurement time, but still retains the original format of the RSA method, which was designed for small patient groups and used special X-ray viewing angles that are different from the clinical standards. 12 A new and emerging form of digital projection radiography is flat panel digital radiography (DR). DR directly converts X-ray energy from a thin film transistor (TFT) medium into electrical signals to generate digital images.…”
Section: Introductionmentioning
confidence: 99%